Pengaruh Interaktivitas Konten Terhadap Respon Audiens (Studi Live Streaming Marapthon By YB) - Salfhaoctha Friemay Aliefia Poetry; Rafi'i Rafi'i; Radyta A. Burhanuddin; Nadiya Fitriyani; Chairunnisa Chairunnisa; Salsabila Firdauza (Asosiasi Dosen Muda Indonesia, 2026)
This research examines the influence of content interactivity on audience responses in the Marapthon by YB live streaming event on YouTube. The study aims to analyze how interactive elements such as live comments, virtual gifts, likes, and Q&A sessions affect the cognitive, affective, and behavioral responses of audiences. Using a quantitative explanatory survey method with 100 respondents selected through random sampling, data were collected via online questionnaires distributed to active viewers of YB’s YouTube channel. The analysis is grounded in the Stimulus Response model and the Uses and Gratifications Theory, which emphasize audience activeness in digital media interactions. The findings indicate that content interactivity has a significant and positive effect on audience response. Among the dimensions of interactivity, real-time comments and virtual gifts have the most dominant influence in stimulating emotional involvement and active participation. This study concludes that interactivity not only strengthens audience engagement but also creates a sense of social presence and collective experience in live streaming environments. The results contribute theoretically to digital communication studies and provide practical insights for content creators and streaming platforms to enhance interactive communication strategies.